Buying And Selling Of Ketaun Kebalit Rice Fields From An Islamic Economic Perspective In Bebie Hall, Praya District: Buying And Selling Of Ketaun Kebalit Rice Fields From An Islamic Economic Perspective In Bebie Hall, Praya District - Mohamad Kholid (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2025)
Community life is inseparable from transactions, one of which is buying and selling. People buy and sell every day, there are many types of transactions carried out by the community. Such as the sale and purchase of rice fields in Bebie Hamlet, Mekar Damai Village, they carry out the sale and purchase with a specified time limit. The seller will sell his rice field to the buyer with the condition that when the specified time has expired, the rice field will return to the seller's property without having to redeem it to the buyer. During the agreed time, the buyer has the right to use and manage the rice field without changing the shape of the rice field. This study aims to determine 1) How is the System and Practice of buying and selling rice fields in Bebie Hamlet, Mekar Damai Village, Central Lombok Regency? 2) What is the view of muamalah fiqh regarding the sale and purchase of rice fields in Bebie Hamlet, Mekar Damai Village, Central Lombok Regency? This research is a qualitative field study with a descriptive qualitative approach. The data source is the research subject, which has a very important position, obtained from primary and secondary data sources. Data collection techniques include interviews, observation, and documentation. Data analysis techniques used by Miles and Huberman include data reduction, data presentation, and drawing conclusions. The results of this study are that the seller will sell his rice field within a specified time limit, when the agreed time the rice field will return to the seller's property without having to redeem it to the buyer. This kind of sale and purchase is an imperfect sale and purchase because the object does not transfer ownership completely forever. The sale and purchase of rice fields in Bebie Hamlet, Mekar Damai Village, Central Lombok Regency has ambiguity in its contract, namely a sale and purchase contract but tends more towards renting. Islamic jurists have different opinions on this matter, some say it is invalid because the rice field does not transfer ownership completely according to the intent of the sale and purchase contract. However, there are also those who allow it based on the basis of mutual consent and has become a custom or habit of the community in Bebie Hamlet, Mekar Damai Village, Central Lombok Regency.